BUSINESS DEVELOPMENT STRATEGY OF B&B PROPERTY COMPANY - Muchammad Rizky Ilham Ramadhan; Nur Nur (Jurnal Manajemen dan Bisnis Performa, 2025)
This study aims to conduct a strategic analysis of the B&B Property company in the context of the property business in Bandung, Indonesia. The background of this research is based on the increasing housing demand in Bandung, as well as the significant economic growth in the property sector. The research method uses a qualitative descriptive approach with the collection of primary data through interviews and questionnaires to company owner and potential customers of B&B Property. Data analysis is conducted through PEST analysis, SWOT analysis, and Business Model Canvas. The results of the study show that B&B Property has strengths in one-stop service, extensive property knowledge, and a positive reputation, but also has weaknesses such as a lack of online presence and inadequate office facilities. Based on the analysis, it is recommended that B&B Property focus on implementing a one-stop service strategy, utilizing social media, improving representative office facilities, and enhancing the quality of human resources. Thus, the company can address challenges and achieve sustainable growth in the property market.